Law, economics, and morality - Zamir, Eyal.; Medina, Barak (New York ; Oxford : Oxford University Press, 2010)
This work examines the possibility of combining economic methodology and deontological morality through explicit and direct incorporation of moral constraints into economic models.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Law and economics; Law -- Philosophy; Law -- Economic aspects; Economics -- Moral and ethical aspects; Law -- Moral and ethical aspects